Antagonism of CGRP Signaling by Rimegepant at Two Receptors - Pan, Kylie S.; Siow, Andrew; Hay, Debbie L.; Walker, Christopher S. (Frontiers in Pharmacology, 2020)
The “gepants” are a class of calcitonin gene-related peptide (CGRP) receptor antagonist molecules that have been developed for the prevention and treatment of migraine. Rimegepant is reported to act at the CGRP receptor, has good oral bioavailability and has had positive clinical trial results. However, there is very little data available describing its receptor pharmacology. Importantly, rimegepant activity at the AMY1 receptor, a second potent CGRP receptor that is known to be expressed in the trigeminovascular system, has not been reported. The ability of rimegepant to antagonize activation of human CGRP, AMY1 and related adrenomedullin receptors was determined in transfected in Cos7 cells. Rimegepant was an effective antagonist at both the CGRP and AMY1 receptor. The antagonism of both CGRP and AMY1 receptors may have implications for our understanding of the mechanism of action of rimegepant in the treatment of migraine.